Health and Welfare Outcomes for Adolescents Following Release from Prison in Queensland, Australia: A Prospective Cohort Study - Rohan Borschmann; Dominique de Andrade; Stuart A. Kinner (Adolescents, 2021)
Background: The transition from prison to the community can be a difficult process and may present different challenges for adolescents (aged < 25 years) compared with their older peers. Methods: Using data from a prospective cohort study in Australia, we compared the health and welfare outcomes of adolescents (aged < 25 years) and adults (aged ≥ 25 years) at 1, 3, and 6 months after release from prison. Results: After one month, adolescents were less likely to be unemployed (adjusted odds ratio (aOR) 0.31; 95% CI 0.15–0.63), report low levels of social support (aOR 0.41; 95% CI 0.21–0.80), or report high psychological distress (aOR 0.50; 95% CI 0.25–0.99). After three months, adults were more likely to have visited a general practitioner (aOR 2.05; 95% CI 1.04–4.07) and adolescents remained less likely to be unemployed (aOR 0.37; 95% CI 0.19–0.74). After six months, adolescents were three times more likely to have used amphetamine-type stimulants (aOR 3.42; 95% CI 1.29–9.09). Conclusions: Adolescents experience different challenges than their older peers when transitioning from prison to the community. Age-specific, integrated support is needed for adolescents during this critical period, including strategies to promote early primary care contact, capitalise on social support networks, and discourage risky substance use.